2019
DOI: 10.1007/s12369-019-00578-z
|View full text |Cite
|
Sign up to set email alerts
|

ZORA Robot Based Interventions to Achieve Therapeutic and Educational Goals in Children with Severe Physical Disabilities

Abstract: This study aimed (1) to examine the contribution of robot ZORA in achieving therapeutic and educational goals in rehabilitation and special education for children with severe physical disabilities, and (2) to discover the roles professionals attribute to robot ZORA when it is used in robot-based play interventions in rehabilitation and special education for children with severe physical disabilities. A multi-centre mixed methods study was conducted among children with severe physical disabilities in two centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Two children (P13 and P14) drew a robot interacting with a child, with their drawings showing clear differences between the appearance of the robot and that of the child. Children with cerebral palsy have shown playfulness and engagement in play activities facilitated by several animal-like and machine-like robotic toys (Air Swimmer, Cubelets, Dash and Dot, Edison and Zoomer) [9], a socially assistive robot [11], ZORA (a version of the NAO robot with software developed for the field of care) [30], and an adapted car-like Lego robot [7]. To date, no studies have compared the acceptance of robots with different appearances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Two children (P13 and P14) drew a robot interacting with a child, with their drawings showing clear differences between the appearance of the robot and that of the child. Children with cerebral palsy have shown playfulness and engagement in play activities facilitated by several animal-like and machine-like robotic toys (Air Swimmer, Cubelets, Dash and Dot, Edison and Zoomer) [9], a socially assistive robot [11], ZORA (a version of the NAO robot with software developed for the field of care) [30], and an adapted car-like Lego robot [7]. To date, no studies have compared the acceptance of robots with different appearances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It has been tested on a cohort of children with disabilities and has been shown to improve the quality of care. 30 However, it was reported that the software required to operate the system was labor intensive for clinicians.…”
Section: Sarsmentioning
confidence: 99%
“…Another Nao-based system is Zora, which is commercially available. It has been tested on a cohort of children with disabilities and has been shown to improve the quality of care 30 . However, it was reported that the software required to operate the system was labor intensive for clinicians.…”
Section: Sarsmentioning
confidence: 99%